Seizures and Munchausen Syndrome by Proxy - J Gordon Millichap (Pediatric Neurology Briefs, 2002)
The prevalence, morbidity and mortality, diagnosis and management of cases of fabricated seizures and child abuse (Munchausen syndrome by proxy (MSbp)) are assessed by pediatricians at the University of Wales College of Medicine, Cardiff, UK.